2013
DOI: 10.1080/14747731.2013.786259
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Globalization and the Global Spread of English: From ‘Separate Fields, Similar Paradigms’ to a Transdisciplinary Approach

Abstract: The global spread of English is an inextricable part of the globalization of culture and media. Despite this close entanglement, theories on the global spread of English have largely been developed within separate fields, such as applied linguistics and sociolinguistics, with relatively limited reference to theories of cultural or media globalization. Conversely, scholars of cultural and media globalization who focus on the role of language rarely refer to work on the global spread of English. Despite this mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…on the labour market) and also to media companies and their potential success on different markets depending on their respective language portfolios. While they have different perspectives, media globalisation studies and linguistic studies on the spread of English reach similar conclusions (Kuppens, 2013): Several studies have identified the importance of language aspects in cross-border media trade (e.g. Collins, 1989; Ksiazek and Webster, 2008).…”
Section: Cross-border Strategies Linguistic (Dis)advantage and Digitisationmentioning
confidence: 92%
“…on the labour market) and also to media companies and their potential success on different markets depending on their respective language portfolios. While they have different perspectives, media globalisation studies and linguistic studies on the spread of English reach similar conclusions (Kuppens, 2013): Several studies have identified the importance of language aspects in cross-border media trade (e.g. Collins, 1989; Ksiazek and Webster, 2008).…”
Section: Cross-border Strategies Linguistic (Dis)advantage and Digitisationmentioning
confidence: 92%
“…The increased prominence of the English language as a form of global communication has expedited the worldwide diffusion and consumption of its often associated cultures (Baker, 2009). This is a worldwide phenomenon that infiltrates all layers of society including the cultural fabric (see, e.g., Kuppens, 2013; Low & Ao, 2018; Pennycook, 2017; Schulzke, 2014) and even local speech communities, e.g., ‘nativisation’ of some English words (Lee & Choe, 2019: 8). However, this spread is not always perceived positively.…”
Section: English Culture and Societymentioning
confidence: 99%